(untitled) (Szociológiai Szemle, 2024)
The present writing wishes to offer certain approaches to the empirical and theoretical study of privatisation and the changes of the internal structure of hierarchical economic organisations. During the course of our investigations we wish to find out among others how the strategic interactions (factional fights and struggles for position, efforts to defend and to acquire status) generated by privatisation have influenced the networks of relationships on the level of workshop and factory. As decision-making is inevitably centralised, or at least has several centres in the organisational hierarchies, it is highly probable that one may often observe such forms of behavior even within economic organisations the objective of which is to influence the decision-makers and/or the rules of decision-making. It is demonstrated that such efforts towards obtaining annuity extending over the entire political and macro economic arena. One of the starting points of our analysis is the hypothesis that there is a constant — overt or covert — struggle in the economic organisations around the distribution of organisational annuity created by the owners of the specific resources of the organisation. The forms of manifestation of the distributive conflict are called the acquisition of annuity and influence within the organisation, and during the course of research we are going to survey the relationships between such efforts towards the acquisition of annuity and influence and privatisation in the sphere of the Hungarian economic organisations.